Atmospheric Chemistry of Oxalate: Insight Into the Role of Relative Humidity and Aerosol Acidity From High‐Resolution Observation. Issue 4 (8th February 2022) - Yang, Chi; Zhou, Shuxin; Zhang, Chunyan; Yu, Mingyuan; Cao, Fang; Zhang, Yanlin
Abstract: Oxalate is the product of the precursors that can eventually be oxidized into oxalate by atmospheric oxidants (O3, etc.) and then redistributed to the particle phase, which has an impact on acid rain, and even the climate. However, we are still unclear about the influence of typical atmospheric oxidants in different phases with different RH and pH on oxalates. Here, we analyzed the effects of typical oxidants at RH ≤ 30%, 30% < RH ≤ 80% of the atmosphere on oxalates in atmospheric particulates based on high‐resolution online observation in Nanjing: the chemical processes of O3, OX (=O3 + NO2 ), and Cl − in different RH all have an important influence on the oxalate level, especially at 30% < RH ≤ 80% with high humidity have greater influence. NO2 only affects the particulate oxalate at RH ≤ 30%; HONO shows a greater effect at RH ≤ 30%, and 30% < RH ≤ 80% in winter and summer, the atmospheric oxidants that dust participates in have little effect. At the same time, we also found the difference between the influence of pH on atmospheric oxalate in winter and summer at RH > 80%, among which high pH is beneficial to the formation of oxalate in summer, while in winter has a greater influence on oxalate at RH ≤ 30%. These results help us to systematically understand the influence and distribution of oxalate in the atmosphere by RH, pH, and typical atmospheric oxidants. Key Points: O3, OX, and Cl − at different humidity ranges in winter and summer have a great influence on atmospheric oxalate Dust in winter and summer have similar effects on atmospheric oxalate levels High pH is beneficial to the formation of oxalate at RH > 80% in summer and at RH ≤ 30% in winter